2018
DOI: 10.1371/journal.pone.0200346
|View full text |Cite
|
Sign up to set email alerts
|

Lower performance of Toxoplasma-infected, Rh-negative subjects in the weight holding and hand-grip tests

Abstract: BackgroundToxoplasma, a protozoan parasite of cats, infects many species of intermediate and paratenic hosts, including about one-third of humans worldwide. After a short phase of acute infection, the tissue cysts containing slowly dividing bradyzoites are formed in various organs and toxoplasmosis proceeds spontaneously in its latent form. In immunocompetent subjects, latent toxoplasmosis was considered asymptomatic. However, dozens of studies performed on animals and humans in the past twenty years have show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In the Czech population, Rh-negative genotype might serve as such predictor. Five previous studies had shown associations between Rh-negativity and psychomotor or cognitive functions [43][44][45][46][47] and other four studies had demonstrated the existence of a relation between Rh-negativity and health [48][49][50][51] . Another large-scale study concluded that Rh-negative mothers give birth to significantly more girls than boys: secondary sex ratio 1.37 in primiparous mothers and 1.23 in all mothers 52 .…”
mentioning
confidence: 99%
“…In the Czech population, Rh-negative genotype might serve as such predictor. Five previous studies had shown associations between Rh-negativity and psychomotor or cognitive functions [43][44][45][46][47] and other four studies had demonstrated the existence of a relation between Rh-negativity and health [48][49][50][51] . Another large-scale study concluded that Rh-negative mothers give birth to significantly more girls than boys: secondary sex ratio 1.37 in primiparous mothers and 1.23 in all mothers 52 .…”
mentioning
confidence: 99%
“…Recent results support the hypothesis that the Rhesus factor polymorphism is maintained in human populations due to a higher resistance or tolerance of heterozygotes to specific diseases (see Introduction). The hypothesis was repeatedly supported by empirical data showing that RhD positivity, and especially RhD heterozygosity, protects people against certain negative effects of toxoplasmosis (Flegr et al, 2008(Flegr et al, , 2018Kankova et al, 2010;Novotna et al, 2008). In line with the Trivers-Willard effect (Trivers and Willard, 1973), our working hypothesis was to expect RhD heterozygous mothers, i.e., mothers with supposedly higher health status, to exhibit a higher secondary sex ratio.…”
Section: Discussionmentioning
confidence: 59%
“…For example, the positive effect of age on performance and intelligence was stronger in RhD positive subjects, whereas the effect of smoking on the number of viral and bacterial diseases was about three times higher in RhD negative subjects. In a different study, Toxoplasma positive RhD negative subjects expressed lower performance in weight-holding and hand-grip tests in comparison with both RhD negative and positive Toxoplasma negative subjects (Flegr et al, 2018). It is clear that faster reaction times or greater stamina conferred a selective advantage in the past, and that they still do in the present.…”
Section: Introductionmentioning
confidence: 94%
“…In conjunction with the I-S-T 2000 R session, participants also engaged in two physical performance tests, provided saliva samples for hormone concentration analysis, and underwent ECG recording. These additional data were utilized in an unrelated study [34].…”
Section: Methodsmentioning
confidence: 99%